Capital Flows, Real Estate, and Local Cycles: Evidence from German Cities, Banks, and Firms. (3rd February 2021) - Bednarek, Peter; Kaat, Daniel Marcel te; Ma, Chang; Rebucci, Alessandro
Abstract: We study how capital flows affects German cities' GDP growth depending on the state of their real estate markets. Identification exploits a policy framework assigning refugees to cities on a quasi-random basis and variation in nondevelopable area for the construction of an exposure measure to real estate market tightness. We estimate that the most exposed cities to real estate market tightness grew at least 1.9 percentage points more than the least exposed ones, cumulatively, from 2009 to 2014. Capital inflows shift credit to firms with more collateral, which leads firms to hire and invest more in response to these shocks.